ByzRev 03.2021.026: Hugh A. G. Houghton – David C. Parker (Hrsg.), Codex Zacynthius (Texts and Studies 21).: Piscataway, NJ: Gorgias Press 2020. - Zawadzki, Konrad F. (The Byzantine Review, 2021)
Hugh A. G. Houghton – David C. Parker (Hrsg.), Codex Zacynthius (Texts and Studies 21). Piscataway, NJ: Gorgias Press 2020. XVII, 317 S. – ISBN: 978-1-4632-4107-0 ( 146.00)